2006
DOI: 10.1074/jbc.m511431200
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cells Are Sensitive Detectors of Bacterial Pore-forming Toxins

Abstract: Epithelial cells act as an interface between human mucosal surfaces and the surrounding environment. As a result, they are responsible for the initiation of local immune responses, which may be crucial for prevention of invasive infection. Here we show that epithelial cells detect the presence of bacterial pore-forming toxins (including pneumolysin from Streptococcus pneumoniae, ␣-hemolysin from Staphylococcus aureus, streptolysin O from Streptococcus pyogenes, and anthrolysin O from Bacillus anthracis) at nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
184
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 159 publications
(196 citation statements)
references
References 32 publications
9
184
1
Order By: Relevance
“…In contrast, van Rossum et al (44) showed that pneumolysin promotes clearance of colonized S. pneumoniae in a TLR4-independent manner. The pore-forming effect of pneumolysin activates p38, contributing to the production of proinflammatory cytokines independent of both TLR2 and TLR4 (52). It is logical that pneumolysin-activated p38 leads to increased bacterial clearance by inducing proinflammatory responses independent of TLR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, van Rossum et al (44) showed that pneumolysin promotes clearance of colonized S. pneumoniae in a TLR4-independent manner. The pore-forming effect of pneumolysin activates p38, contributing to the production of proinflammatory cytokines independent of both TLR2 and TLR4 (52). It is logical that pneumolysin-activated p38 leads to increased bacterial clearance by inducing proinflammatory responses independent of TLR.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, 500 ng/ml pneumolysin induces pronounced cytotoxicity (60% by LDH assay) but significantly lower MUC5AC expression. Recently, Ratner et al (52) demonstrated that pneumolysin increases cell membrane permeability by forming membrane pores, and the induced osmotic stress activates p38 independent of both TLR2 and TLR4. Implied therein is that activation of p38 is cytotoxicity-mediated and independent of TLR signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, sublytic concentrations of ␣-toxin from S. aureus, streptolysin O from Streptococcus pyogenes, anthrolysin O from Bacillus anthracis, and pneumolysin from Streptococcus pneumoniae, have been shown to stimulate MAP kinase signaling (Ratner et al, 2006). In addition, pneumolysin, as well listeriolysin O from Listeria monocytogenes and perfringolysin from Clostridium perfringes, have been shown to induce histone modifications within target host cells (Hamon et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, generic membrane damage does not seem to be sufficient to induce Akt dephosphorylation, because the treatment of bladder cells with 0.0025 or 0.025% saponin, which forms relatively large pores in host cell membranes, had no effect on Akt (unpublished data). Interestingly, a recent report indicated that sublytic concentrations of pore-forming toxins can trigger osmotic stress in target epithelial cells (Ratner et al, 2006), and osmotic stress has been shown to modulate Akt activation via effects on phosphatases (Meier et al, 1998). These studies suggest a scenario in which osmotic stress induced by small pore-forming toxins may stimulate host protein phosphatase activation and subsequent dephosphorylation of Akt, a possibility that is supported by our results using dextran (M r ϳ 150,000), which blocks HlyA pores and limits osmotic stress.…”
Section: Discussionmentioning
confidence: 99%
“…This latter assessment, although well-accepted, does not, however, detect the sub-lytic activity which underpins the potentially harmful pro-inflammatory activity of the toxin with other cell-types such as neutrophils 11 and epithelial cells. 12 In the current study, we have therefore compared the effects of WT/PLY and Δ6 PLY on several Ca 2+ -dependent pro-inflammatory activities of human neutrophils in vitro.…”
Section: Introductionmentioning
confidence: 99%